Constraints in Marketing Hoplo Affected Sal Timber - Tewari, Rachna; Kala, R. P. (Indian Forester, 2007)
The objective of the study was to find out the constraints in marketing borer (Hoplocerambyx spinicornis) affected Sal timber by Uttarakhand Forest Development Corporation (UFDC). A holistic approach was taken to include the study of all the stakeholders. Market demand and utility of Sal timber was also examined with reference to the Sales and Marketing system of UFDC. The Hoplo affected timber is certainly selling at a lower price than the cost of production thereby becoming a source of loss to the UFDC. Not only the Hoplo infestation, but there are many interdependent reasons for the difficulties in disposing off the Hoplo infested Sal at remunerative prices. A change in the marketing system through value addition and finding out alternative uses for such timber would certainly increase the utility and improve the financial return to the Corporation.